The Effect of Additional Employee Income (TPP) on ASN Discipline at the Medan City Education and Culture Office with Work Motivation as a Mediation Variable - Manik, Emmy Kiki; Aisyah, Siti; Turnip, Kaiman (Yayasan Sembilan Pemuda Indonesia, 2025)
The amount of Additional Employee Income will be calculated again proportionally based on the number of attendance and absences under certain conditions and divided by the number of working days in the month in question. So that civil servants who do not attend work for no apparent reason will get a fine deducted from their TP P. This is felt to have a fairly heavy effect considering the amount of Additional Employee Income is quite large in the salary component. Currently, the attendance recording process is carried out conventionally using an attendance journal signed by civil servants every time they attend work. This conventional process is considered quite burdensome, considering that each Regional Apparatus Organization (OPD) must provide an official report to the Regional Civil Service Agency for the process of disbursing TPP for civil servants. However, it is not known whether additional employee income (TPP) affects ASN discipline on ASN’s work motivation through mediation variables. The study examined the influence of TPP on ASN Discipline on ASN work motivation through mediation variables. This explanatory quantitative research involved 120 Civil Servants at the Medan City Education and Culture Office. Data analysis uses a Structural Equation Model (SEM) operated through the SmatPLS program. The results show that TPP is able to mediate work motivation and affect employee discipline.